Attitudes to death: some historical notes - Boyd, K. (1977)
Men have been talking of death from time immemorial - sometimes sublimely in prose and poetry, in painting and sculpture and in music - till silence seemed to fall in the recent past. Now men are again talking about death - interminably but colloquially. They talk on television, on the radio, in books and in pamphlets. Dr Kenneth Boyd therefore finds it entirely timely to offer this historical sketch of attitudes to death. The earlier part of his paper covers fairly familiar ground but his final and longest section on the work of a social historian, Philippe Ariès, may be new to many. Ariès is reinterpreting the long history of attitudes to death in a form which may well interest those who today are concerned with helping modern man to accept his own death - death which still, for most people, is the death of another, not of oneself.